Control of the banana Anthracnose Pathogen using Antagonistic Microorganisms - Khleekorn, S.; McGovern, R. J.; Wongrueng, S. (International Journal of Agricultural Technology, 2015)
This study aimed to determine the biological control abilities of selected antagonistic microorganisms to inhibit the growth of Colletotrichum musae, the causal agent of anthracnose disease found in banana fruits. In previous studies, Pantoea agglomerans and Enterobacter sp. showed effectiveness in controlling the anthracnose disease. It was found that the maximal germination rate of C. musae was 93.35 % at 31 °C after 35 h. The inhibition of the conidial germination of C. musae by P. agglomerans and Enterobacter sp. occurred 1 h after incubation at 31 °C. At 50 % mixture of P. agglomerans or Enterobacter sp. with PDA showed effectiveness in inhibiting conidial germination by 97.23% and 88.05%, respectively, and the capability to inhibit the mycelial growth of the fungus by 99.61 % and 99.23 %, respectively. The study of direct parasitism showed evidence of antagonist cells around the fungal hyphae, but it did not show that the hyphae became irregular in shape or twisted. Based on the in vivo study, a selected Enterobacter sp. antagonist applied on a banana every week before harvest showed the most effectiveness in controlling anthracnose, with 87.6 % inhibition.